Imidazole-Thiosemicarbazide Derivatives as Potent Anti-Mycobacterium tuberculosis Compounds with Antibiofilm Activity - Adrian Bekier; Malwina Kawka; Jakub Lach; Jarosław Dziadek; Agata Paneth; Justyna Gatkowska; Katarzyna Dzitko; Bożena Dziadek (Cells, 2021)
Mycobacterium tuberculosis (Mtb) is an intracellular pathogenic bacterium and the causative agent of tuberculosis. This disease is one of the most ancient and deadliest bacterial infections, as it poses major health, social and economic challenges at a global level, primarily in low- and middle-income countries. The lack of an effective vaccine, the long and expensive drug therapy, and the rapid spread of drug-resistant strains of Mtb have led to the re-emergence of tuberculosis as a global pandemic. Here, we assessed the in vitro activity of new imidazole-thiosemicarbazide derivatives (ITDs) against Mtb infection and their effects on mycobacterial biofilm formation. Cytotoxicity studies of the new compounds in cell lines and human monocyte-derived macrophages (MDMs) were performed. The anti-Mtb activity of ITDs was evaluated by determining minimal inhibitory concentrations of resazurin, time-kill curves, bacterial intracellular growth and the effect on biofilm formation. Mutation frequency and whole-genome sequencing of mutants that were resistant to ITDs were performed. The antimycobacterial potential of ITDs with the ability to penetrate Mtb-infected human macrophages and significantly inhibit the intracellular growth of tubercle bacilli and suppress Mtb biofilm formation was observed.